Molecular insights into mechanisms underlying thermo-tolerance in tomato - Singh, Achuit K.; Mishra, Pallavi; Kashyap, Sarvesh Pratap; Karkute, Suhas G.; Singh, Prabhakar Mohan; Rai, Nagendra; Bahadur, Anant; Behera, Tusar K. (Frontiers in Plant Science, 2022)
Plant productivity is being seriously compromised by climate-change-induced temperature extremities. Agriculture and food safety are threatened due to global warming, and in many cases the negative impacts have already begun. Heat stress leads to significant losses in yield due to changes in growth pattern, plant phonologies, sensitivity to pests, flowering, grain filling, maturity period shrinkage, and senescence. Tomato is the second most important vegetable crop. It is very sensitive to heat stress and thus, yield losses in tomato due to heat stress could affect food and nutritional security. Tomato plants respond to heat stress with a variety of cellular, physiological, and molecular responses, beginning with the early heat sensing, followed by signal transduction, antioxidant defense, osmolyte synthesis and regulated gene expression. Recent findings suggest that specific plant organs are extremely sensitive to heat compared to the entire plant, redirecting the research more towards generative tissues. This is because, during sexual reproduction, developing pollens are the most sensitive to heat. Often, just a few degrees of temperature elevation during pollen development can have a negative effect on crop production. Furthermore, recent research has discovered certain genetic and epigenetic mechanisms playing key role in thermo-tolerance and have defined new directions for tomato heat stress response (HSR). Present challenges are to increase the understanding of molecular mechanisms underlying HS, and to identify superior genotypes with more tolerance to extreme temperatures. Several metabolites, genes, heat shock factors (HSFs) and microRNAs work together to regulate the plant HSR. The present review provides an insight into molecular mechanisms of heat tolerance and current knowledge of genetic and epigenetic control of heat-tolerance in tomato for sustainable agriculture in the future. The information will significantly contribute to improve breeding programs for development of heat tolerant cultivars.